(untitled) (International conference on multidisciplinary science, 2023)
This article explores the life and work of G.A. Pugachenkova, a renowned archaeologist and art historian. Born in 1925, Pugachenkova made significant contributions to the fields of Central Asian archaeology and the art of the Silk Road. Through meticulous excavations and interdisciplinary research, she unraveled the cultural exchanges, artistic traditions, and historical contexts of ancient civilizations. Her findings, documented in numerous publications, have shaped our understanding of Central Asia’s archaeological and artistic heritage. Pugachenkova’s dedication and passion continue to inspire scholars and enthusiasts, leaving a lasting impact on the exploration and preservation of this captivating cultural legacy.